Financial Performance Analysis Before and After Initial Public Offering (Study on Banking Companies that Listed on the Indonesia Stock Exchange Period 2010-2018) - Devid Subekti; Yusuf Imam Suja'i (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Initial Public Offering (IPO) is the first activity of a company to offer shares to the general public. The IPO was carried out with the aim of gaining access to funding that could be used as additional capital for the development and resilience of the company. The focus of this research is to find out and find empirical evidence of differences in the financial performance of banks between before the IPO and after the IPO. The financial ratios studied are ROA, RORA, NIM, CAR, ROE, LDR, and NPM. This research is a type of quantitative descriptive research. The population used in this study are companies from the banking industry listed on the Indonesia Stock Exchange from 2010 to the end of 2018. The sampling technique is purposive sampling so that 16 banking companies have IPOs and are listed on the IDX. The results showed that judging from the ROA value there was no effect of the IPO on financial performance; based on RORA value there is no effect of IPO on financial performance; based on the CAR ratio there is no IPO effect on financial performance; based on the NIM ratio there is no effect of the IPO on the company's financial performance; based on the ROE ratio there is an IPO effect on the company's financial performance; based on the LDR ratio there is no effect of the IPO on the company's financial performance; based on the NPL ratio there is a significant effect of the IPO on financial performance.